Crise e fascistização:Brasil, 2014-2018 - Sanchez, Mariano Luis (2023)
This thesis focuses on the process of fascistization that plagued Brazil from 2014 to 2018. It seeks to analyze the factors that combined to produce, over this period, the great social support given to the authoritarian government project represented by the so-called Bolsonarism. In general terms, the process of fascistization is thought here from the rise of authoritarian propaganda, promoting intolerance, inciting aggressiveness and the manifestation of symbolic for political-ideological reasons that go unpunished due to the omission or complicity of state institutions that should curb or penalize them. What distinguishes Fascism from other forms of political authoritarianism is the mobilization of masses, mainly a petty-bourgeois base of supporters, and the organization of shock troops that carry out illegal violence. Therefore, the formation of Fascist masses is the means by which an authoritarian project engenders broad social support. In this work, we study the mediation between authoritarian discourse and its social reception from the perspective of Social Psychology, which focuses on the leader-mass relationship. Since we maintain that the process of fascistization in the Brazilian case began before the appearance of the figure of the authoritarian leader, we consider that the narrative produced by the mainstream media, during the aforementioned period, was configured as a proto-discourse of the leader, amplifying the political and economic crisis then ongoing. We argue that the mainstream media’s narrative had a strongly fascistizing effect insofar as it combined hate speech and fear speech, significantly impacting audience emotions, and thus spreading a social climate of moral indignation and political intolerance. To the extent that it promoted the formation and mobilization of the masses, it fed political instability and the erosion of democratic institutions. However, as the power of influence of the Fascist discourse (media in this case) is not absolute, its success depends on finding correspondence with a potentially authoritarian personality type already present in society. In this sense, we argue that the neoliberal management of contemporary capitalism produces a subjectivity prone to supporting authoritarian solutions to political, economic or social problems and crises. In this sense, the Fascist discourse is thought of as a device that activates the latent authoritarian personality in society, the result of a socioeconomic objectivity characterized by the superexploitation of the worker, by the utmost precariousness of work or, in the extreme, their total marginalization. We dedicate the last part of this work to studying the deeper causes of the emergence of discourses, movements and leaderships –– quite international in their nature –– imbued with neo-Fascist characteristics, demonstrating the continuity, rather than the rupture, between the crisis or exhaustion of the neoliberal project and the resurgence of Neo-Fascism as a response to the need to manage the ever-growing marginalized masses in the context of the ever-deepening structural crisis of capital. In the final considerations, we point out that every process of fascistization is the result of the decision of the most powerful fractions of the dominant economic interests, and for this reason, Fascism will always be a concrete possibility in every capitalist society.